Validation of a CT image based software for three-dimensional measurement of acetabular cup orientation. - Wassilew GI; Janz V; Heller M; Wenzl M; Perka C; Hasart O; Wassilew, Georgi I; Janz, Viktor; Heller, Markus; Wenzl, Marcus; Perka, Carsten; Hasart, Olaf (Technology & Health Care, 2011)
The purpose of our study was to develop a simple and reproducible method for calculating post-operative acetabular cup position based upon computed tomographic images. Next, we sought to examine the reliability, objectivity and accuracy of this method. We developed a 3D CT evaluation software based upon Amira® (data visualisation, analysis and modelling software) to calculate the abduction and anteversion of the acetabular cup relative to the APP (anterior pelvic plane). To test the accuracy of the method, we constructed a special phantom pelvic model as the gold standard, in which the acetabulum was mounted at various abduction and anteversion angles that had previously been measured digitally. This phantom was then CT scanned in 12 different cup positions (30° to 50° abduction, 0° to 30° anteversion) and then evaluated using the 3D CT evaluation software. In addition, we also examined the reliability and objectivity of this method in 10 patients following implantation of a hip prosthesis, as a clinical trial. We observed an average accuracy of the 3D CT evaluation software of −0.3° (range −1.4° to 1.3°; SD 0.6°) for abduction and 0.2° (range −1.4° to 1.4°; SD 0.6°) for anteversion compared with the gold standard. Moreover, a high intra -and interindividual agreement in the resulting ICC well above 0.8 for abduction and abduction values in the phantom study and the clinical trial were observed. This study found that the 3D CT evaluation software provides high reliability, objectivity and accuracy. Thus, the 3D CT software is a method that permits very precise evaluation of the post-operative cup position independent of patient positioning or pelvic tilt.